2022
DOI: 10.1186/s12951-022-01425-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain-targeted heptapeptide-loaded exosomes attenuated ischemia–reperfusion injury by promoting the transfer of healthy mitochondria from astrocytes to neurons

Abstract: Background The exchange of mitochondria reportedly plays an important role in cell–cell communication in the central nervous system (CNS). The transfer of fragmented and dysfunctional astrocytic mitochondria into neurons and subsequent mitochondrial fusion often cause serious neuronal damage and cerebral ischaemic injury. Methods In this study, we prepared macrophage-derived exosomes laden with heptapeptide (Hep) as a dynamin-related protein-1 (Drp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The crosstalk mechanism of mitochondria between cells provides potential hints for regulating neuronal survival. Our previous research also confirmed that after stroke, injured mitochondria from activated type A1 astrocytes can lead to the aggravation of neuronal damage and prolonged recovery after ischemia stroke [22].…”
Section: Discussionsupporting
confidence: 76%
“…The crosstalk mechanism of mitochondria between cells provides potential hints for regulating neuronal survival. Our previous research also confirmed that after stroke, injured mitochondria from activated type A1 astrocytes can lead to the aggravation of neuronal damage and prolonged recovery after ischemia stroke [22].…”
Section: Discussionsupporting
confidence: 76%
“…In China, SMD has been widely used to treat cough variant asthma, post-infection cough, bronchitis, and other airway diseases [ 16 , 17 ]. Although studies revealed that SMD can attenuate asthma by regulating the expression of inflammatory mediators such as of INF- γ , IL-4, IL-10, IL-13, and TNF- α [ 18 , 19 ], the exact mechanism underlying its protective effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…EXO-Hep increased neuronal viability and neuroprotection against ischemic stroke by ameliorating the mitochondrial function of astrocytes with the assistance of Drp1/fission1 interaction inhibition. [205,206] Xu et al developed MSC-EVs encoding the tyrosine phosphatase-2 (SHP2) gene (MSC-EVs-SHP2) to restore neuronal mitophagy through high expression of SHP2. MSC-EVs-SHP2 passed through the BBB of AD mice and restored neuronal mitophagy through the high expression of SHP2, thereby reducing the accumulation of amyloid-𝛽(A𝛽)-42 (Figure 11B) and reducing neuroinflammation, oxidative stress, and neuronal apoptosis.…”
Section: Regulating Mitochondrial Dynamics and Mitophagymentioning
confidence: 99%